Transactional Sex With Regular and Casual Partners Among Young Men Who Have Sex With Men in the Detroit Metro Area. (May 2017) - Bauermeister, José A.; Eaton, Lisa; Meanley, Steven; Pingel, Emily S.; ,
Transactional sex refers to the commodification of the body in exchange for shelter, food, and other goods and needs. Transactional sex has been associated with negative health outcomes including HIV infection, psychological distress, and substance use and abuse. Compared with the body of research examining transactional sex among women, less is known about the prevalence and correlates of transactional sex among men. Using data from a cross-sectional survey of young men who have sex with men (ages 18-29) living in the Detroit Metro Area ( N = 357; 9% HIV infected; 49% Black, 26% White, 16% Latino, 9% Other race), multivariate logistic regression analyses examined the association between transactional sex with regular and casual partners and key psychosocial factors (e.g., race/ethnicity, education, poverty, relationship status, HIV status, prior sexually transmitted infections [STIs], mental health, substance use, and residential instability) previously identified in the transactional sex literature. Forty-four percent of the current sample reported engaging in transactional sex. Transactional sex was associated with age, employment status, relationship status, and anxiety symptoms. When stratified, transactional sex with a regular partner was associated with age, educational attainment, employment status, relationship status, anxiety, and alcohol use. Transactional sex with a casual partner was associated with homelessness, race/ethnicity, employment status, and hard drug use. The implications of these findings for HIV/STI prevention are discussed, including the notion that efforts to address HIV/STIs among young men who have sex with men may require interventions to consider experiences of transactional sex and the psychosocial contexts that may increase its likelihood.